2023
DOI: 10.1039/d3dt03137c
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of dysprosium(iii) cubanes in a metal–organic framework with an ecu topology and slow magnetic relaxation

Dong Shao,
Yi Wan,
Jiong Yang
et al.

Abstract: A rare dysprosium(iii) metal–organic framework constructed using dysprosium(iii) cubanes as secondary building units has been reported to exhibit field-supported single-molecule magnet (SMM) behavior and an unprecedented ecu topology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…[31][32][33][34] Very recently, we found that the classical 2,5-dioxodo-1,4benzenedicarboxylate (H 4 dobdc) is a powerful ligand to prepare lanthanide coordination polymers with hydrophilic groups and coordination water molecules. 35,36 The bifunctional derivative of salicylic acid, H 4 dobdc, exhibits both intra-and intermolecular proton transfer, along with redox-active conversion between its enol and keto isomers. Its structural rigidity and four pH-dependent extractable protons render H 4 dobdc a compelling multifunctional organic ligand for generating stable and rigid highdimensional MOFs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34] Very recently, we found that the classical 2,5-dioxodo-1,4benzenedicarboxylate (H 4 dobdc) is a powerful ligand to prepare lanthanide coordination polymers with hydrophilic groups and coordination water molecules. 35,36 The bifunctional derivative of salicylic acid, H 4 dobdc, exhibits both intra-and intermolecular proton transfer, along with redox-active conversion between its enol and keto isomers. Its structural rigidity and four pH-dependent extractable protons render H 4 dobdc a compelling multifunctional organic ligand for generating stable and rigid highdimensional MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44] As a result, we reported two isostructural lanthanide coordination chains with slow magnetic relaxation (Dy 3+ ) and magnetocaloric effect (Gd 3+ ). 35 Additionally, a Dy(III) MOF, utilizing Dy(III) cubanes as secondary building units, was found to display slow magnetic relaxation behavior under applied dc field and an rare ecu topology. 36 With its carboxyl and phenolic hydroxyl groups, the H 4 dobdc ligand is structurally effective in forming proton-conducting coordination polymers based on our studies and also a potential ligand for designing dual-functional Ln-MOFs.…”
Section: Introductionmentioning
confidence: 99%